Efficacy of Lincomycin in Chronic Hematogenous Osteomyelitis in Children - Musoyev Sodiqjon Toyirovich (Journal of Science in Medicine and Life, 2024)
Osteomyelitis in children is a pathological condition in which purulent damage is caused to all bone structures, as well as to the bone marrow, along with the surrounding tissues. The disease in childhood is characterized by an acute onset, rapid development of symptoms and severe pain. Pediatricians, pediatric orthopedic traumatologists, surgeons and other specialized specialists are involved in identifying the symptoms of bone osteomyelitis in children, searching for its causes and treating it. Most of the cases detected are between 6 and 14 years of age. At an early age, the main peak is observed in children under one year of age, and boys are twice as likely to have osteomyelitis than girls. Pathology can cover any type of bone structure, but it is mainly diagnosed with damage to tubular femoral, humerus and less common tibial bones. Childhood osteomyelitis is one of the most dangerous diseases of the musculoskeletal system: the probability of various complications, disability and even death of the child is very high.